Biological activities of eco-friendly synthesized Hantzsch adducts - Pacheco, Samira R; Braga, Taniris C; da Silva, Daniel L; Horta, Livia P; Reis, Fabiano S; Ruiz, Ana Lucia T G; de Carvalho, Joao E; Modolo, Luzia V; de Fatima, Ângelo (Medicinal chemistry (Shp-sariqah, United Arab Emirates), 2013)
Fourteen Hantzsch adducts with different substituents at the C-4 position were synthesized through multicomponent reactions by using citric or lactic acid as catalysts. To the best of our knowledge, this is the first report on the synthesis of such a class of compounds based on multicomponent reactions catalyzed by non-toxic organic acids. The potential to scavenge reactive nitrogen/oxygen species (RNS/ROS) and the ability to inhibit cancer cell growth were then investigated. Among the synthesized compounds, adduct 15 was the most promising free radical scavenger, while adduct 20 was shown to have a wider spectrum of action on the cancer cells studied. These results highlight Hantzsch adducts as lead compounds for obtaining new free radical scavengers and anticancer agents.